(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study explores the intricate interplay between regulatory reforms and business transformation in the context of Indian industries. Specifically, the research delves into recent changes in taxation, labor laws, and corporate governance, aiming to discern their impact on organizational strategies, structures, and operations. Utilizing a mixed-methods approach, which involves qualitative analyses of regulatory shifts and quantitative assessments of business performance metrics, the study seeks to provide holistic insights. By examining sectoral variations and conducting in-depth interviews and case studies, this research contributes original knowledge to academic scholarship and imparts practical implications for businesses navigating dynamic regulatory landscapes. The anticipated findings aim to illuminate the adaptability and resilience of Indian industries, thereby advancing our understanding of the complex relationship between regulatory reforms and business transformation in this distinctive context.